2020
DOI: 10.1080/09548963.2020.1827931
|View full text |Cite
|
Sign up to set email alerts
|

“A plague upon your howling”: art and culture in the viral emergency

Abstract: Before the DelugeThe COVID-19 pandemic is global, but the globe is not homogenous. Whilst we all recognise the signs from the newsfeeds -lockdowns, flattening curves, flat-out medical services, first and second waves, disrupted travel, disrupted employment, masking/not-masking, solidarities/ scapegoating -these are refracted through very different political-cultural configurations. Readers will no doubt be all too familiar with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 10 publications
2
59
0
2
Order By: Relevance
“…For example, our initial research showed that inconsistent government support meant that while some creative freelancers received financial support, others in unstable freelance job situations (e.g., those new to working in the cultural industries with less social and symbolic resources than those who are more established) or those with portfolio careers (e.g., balancing PAYE and noncultural work with freelance cultural work) were less likely to receive funding. Although small scale, our new findings build on this to show that those who began the pandemic in an insecure position continued to experience increasing hardship as the pandemic continued, as has been acknowledged elsewhere (Banks & Connor, 2020). Participants who did not receive adequate funding initially or who were ineligible (the ones also more likely to be already working within a landscape of uncertain job prospects) were those who either left their artistic career to work in a different sector or shifted the focus of their work into a different role within the cultural industries, experiencing mental health consequences as a result.…”
Section: Discussionsupporting
confidence: 54%
“…For example, our initial research showed that inconsistent government support meant that while some creative freelancers received financial support, others in unstable freelance job situations (e.g., those new to working in the cultural industries with less social and symbolic resources than those who are more established) or those with portfolio careers (e.g., balancing PAYE and noncultural work with freelance cultural work) were less likely to receive funding. Although small scale, our new findings build on this to show that those who began the pandemic in an insecure position continued to experience increasing hardship as the pandemic continued, as has been acknowledged elsewhere (Banks & Connor, 2020). Participants who did not receive adequate funding initially or who were ineligible (the ones also more likely to be already working within a landscape of uncertain job prospects) were those who either left their artistic career to work in a different sector or shifted the focus of their work into a different role within the cultural industries, experiencing mental health consequences as a result.…”
Section: Discussionsupporting
confidence: 54%
“…A historical event is understood in terms of its effect on structures of society via transforming exiting cultural schemas, resource distribution and power relations (Sewell 1996). Indeed, the pandemic is an historical event of our times, and many commentators believe that it presents a historical choice point not just in cultural policy but also in neoliberal capitalist economy (Banks 2020;Banks and O'Connor 2021;Meyrick and Barnett 2021). Some of them note that the change is overdue, pinpointing the structural and historical roots (the precarity of cultural work and the instrumental cultural policy) of the current hardship (or 'low immunity') of the cultural sector even before the pandemic (Banks 2020, 650;Comunian and England 2020;Eikhof 2020).…”
Section: Cultural Policy Crisis and Critical Juncturementioning
confidence: 99%
“…Yet, the available writings on Covid-19 and cultural policy tend to regard the current period, explicitly or implicitly, as a significant moment in which ruptures have emerged in the dominant ways of doing cultural policy unravelling its existing structures, institutions and relations (Meyrick and Barnett 2021, 1). Aspiring for fundamental reshaping of cultural policy, commentators demand it to reorient from economic values towards public values and to demonstrate more care for the cultural sector and its workforce (Banks 2020;Banks and O'Connor 2021;Joffe 2021;Meyrick and Barnett 2021;Serafini and Novosel 2021). Keen to 'reimagine [the creative economy] more progressively' and explore 'a possible new world' (Banks 2020, 651-2), they themselves are engaged in the process of symbolic interpretation that defines the pandemic as a 'historical event' (Sewell 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Their findings reveal that although the surveys bring out visible critical factors, invisible personal and long-term sustainability has not been addressed. Banks and O'Connor (2021), in their introduction "'A Plague Upon your Howling': Art and Culture in the Viral Emergency" to a special issue of Cultural Trends, trace the international emergence of state policy in relation to the cultural and creative sector in the wake of COVID-19. In their view, the induction of the cultural and creative sectors in the industry and their entry into the market 40 years ago has made them vulnerable to the instabilities of the market economy and that state cultural policies are often influenced by the CCIs' new status as industry where the market is expected to regulate the demand and supply curve.…”
Section: Precarity Ccis and Covid-19mentioning
confidence: 99%